HUBUNGAN SPIRITUAL DENGAN KUALITAS HIDUP PASIEN HIV/AIDS - Syahrul Handoko Nainggolan; Ratna Dewi; Christina Magdalena T.Bolon; Rostinah Manurung; Sarmaida Siregar; Nixson Manurung (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
The body can cause a decrease in the immune system, which can lead to AIDS. HIV/AIDS sufferers oftenexperience various complex problems in all aspects, including biological, psychological, social, andspiritual aspects. Spiritual problems that often arise in sufferers include blaming God, refusing toworship, disturbances in worship, and spiritual distress. Spiritual distress will impact their healthcondition in the form of a decreased quality of life because they have not accepted their illness and thetreatment that must be undergone. The purpose of this study was to determine the relationship betweenspirituality and the quality of lifeof HIV/AIDS sufferers at the RSU Imelda Pekerja IndonesiaMedan.This type of research is a quantitative approach with a cross-sectional research design. The sample in thestudy was determined by non-probability sampling with a purposive sampling technique of 111 HIV/AIDSpatients. Data analysis used the chi-square test. The results of the study indicate a relationship betweenspirituality and the quality of life of HIV/AIDS patients. It is recommended that the hospital use this asinformation and basic data regarding howspirituality applies to the quality of life of HIV/AIDS patientsso that the hospital can make policies to provide better services to HIV/AIDS patients undergoingtreatment atRSU Imelda Pekerja IndonesiaMedan.